ANALISIS KEBUTUHAN PEGAWAI BERDASARKAN LATAR BELAKANG PENDIDIKAN DI SEKRETARIAT DINAS PENDIDIKAN PROVINSI JAWA BARAT - Szasza Nurfitri (Jurnal Tata Kelola Pendidikan, 2021)
This research is entitled "Analysis of Employee Needs based on Educational Background at the Secretariat of the Education Office of West Java Province". The purpose of this study was to analyze the number of employee needs based on educational background at the Secretariat of the Education Office of West Java Province. This type of research uses a descriptive method with a qualitative approach. Data collection techniques used in this study were observation, interviews, documentation studies and triangulation. The results of the study show that the job descriptions of each subsection at the Secretariat of the West Java Provincial Education Office are clear and listed in the job analysis document. Based on the analysis of employee needs, the positions experiencing a shortage of employees include the positions of Data Manager, Salary Manager, Financial Manager, Application Data Processor and Financial System Data Manager, Financial Statement Compiler, Financial Verifier, State Property Manager, Personnel Manager, and Needs Preparer. Inventory. Judging from the comparison of needs and supplies, the number of staff shortages for these positions is 47 people, with details of the position of Data Manager as many as 1 person, Salary Manager as many as 6 people, Financial Manager as many as 15, Application Data Processor and Financial System Data Manager as many as 3 people. , 1 person in preparing Financial Statements, 7 in Financial Verifier, 4 in State Property Manager, 9 in Personnel Manager, and 1 in Inventory Needs Compiler. Therefore, it is better to add employees as needed based on the relevant educational background as one of the job requirements.